Analgesic Efficacy of Intravenous Ibuprofen in the Treatment of Postoperative Acute Pain: A Phase III Multicenter Randomized Placebo-ControlledDouble-Blind Clinical Trial - Hong-Su Zhou; Ting-Ting Li; Yu Pi; Ting-Hua Wang; Fei Liu; Liu-Lin Xiong (Pain Research and Management)
Objective. To evaluate the analgesic efficacy and safety of different does of intravenous ibuprofen (IVIB) in the treatment of postoperative acute pain. Methods. Patients with an intravenous (IV) patient-controlled analgesia device after abdominal or orthopedic surgery were randomly divided into placebo, IVIB 400 mg, and IVIB 800 mg groups. The first dosage of study medicines was given intravenously 30 minutes (min) before surgery ended, followed by six hours (h) intervals for a total of eight doses following surgery. The demographic characteristics and procedure data, cumulative morphine consumption, the visual analog scale (VAS), the area under the curve (AUC) of VAS, patient satisfaction score (PSS), the rates of treatment failure (RTF), and adverse events (AEs) and serious adverse event (SAEs) were recorded during the period of trial. Result. A total of 345 patients were enrolled in the full analysis set (FAS), and of 326 participants were valid data set (VDS). Demographic characteristics, disease features, and medical history of patients were not significantly different between groups. Total morphine consumption of the IVIB 400 mg group (11.14 ± 7.14 mg; P = 0.0011) and the IVIB 800 mg group (11.29 ± 6.45 mg; P = 0.0014) was significantly reduced compared with the placebo group (14.51 ± 9.19 mg) for 24 h postoperatively, there was no significant difference between the IVIB 400 mg and IVIB 800 mg groups (P = 0.9997). The placebo group had significantly higher VAS and the AUCs of VAS than those in the IVIB 400 mg and the IVIB 800 mg groups at rest and movement for 24 h postoperatively (P < 0.05), and there was no significant difference between the IVIB 400 mg and IVIB 800 mg groups (P > 0.05). RTF was slightly higher in the placebo group than IVIB 400 mg group and 800 mg group, and no statistical significance (P < 0.690). PSS in the IVIB 400 mg (P = 0.0092) and the IVIB 800 mg groups (P = 0.0011) was higher than the placebo group for pain management, there was also no significant difference between the IVIB 400 mg and IVIB 800 mg groups (P = 0.456). The incidence of RTF (P = 0.690) and AEs (P > 0.05) were not different among the three groups. Conclusion. Intermittent IV administration of ibuprofen 400 mg or 800 mg within 24 h after surgery in patients undergoing abdominal and orthopedic surgery significantly decreased morphine consumption and relieved pain, without increasing the incidence of AEs.